Security-related Provisions in IPR Laws in India - Gupta, V.K. (DESIDOC Journal of Library & Information Technology, 2010)
The paper highlights the security-related provisions in IPR laws in India. There are no specific provisions related to national security in the laws on copyright, trademark, and geographical indication. It describes the provisions in the laws relating to patents, designs, integrated circuits, and plant varieties. The components of the Competition Act and the Information Technology Act relevant to the application of the acts keeping in mind the security of the country have also been included. The paper also points out the importance of other issues in the management of IPRs in defence like protection of confidential information, use of patent information in R&D, and sharing of IPRs during collaboration and the joint ventures in the development of technology. http://dx.doi.org/10.14429/djlit.27.4.181